Celebrating Al and Rose Watkins' 40th Wedding Anniversary - Watkins, Howard::::::::: (1983)
Rose Watkins holding awaken Robin Watkins; Helen Serfosa hugging Adam Watkins; red roses in foreground 207 Geneva Ave. #B